The influence of thermal expansion on flow past an inclined accelerated sectional plate with persistent mass diffusion - Nagarajan, Gnanavel; Sundar Raj, M.; Muthucumaraswamy, R. (Zielona Góra: Uniwersytet Zielonogórski)
In this article, we examined the solution of a homogeneously intensified isothermal inclined infinite plate with constant temperature. The plate is elevated to TW, and the species accumulation is enhanced at a consistent speed. Under appropriate boundary conditions, the non-dimensional guiding formulae are remedied using the Laplace transform procedure.
Keywords: thermal expansion; mass diffusion; accelerated; inclined plate; isothermal